2019
DOI: 10.1016/j.isci.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1 Regulates Extrasynaptic Targeting of NMDARs and Neuronal Vulnerability Toward Excitotoxicity

Abstract: Summary N-methyl-D-aspartate (NMDA) receptor (NMDAR) is highly compartmentalized in neurons, and its dysfunction has been implicated in various neuropsychiatric and neurodegenerative disorders. Recent failure to exploit NMDAR antagonization as a potential therapeutic target has driven the need to identify molecular mechanisms that regulate NMDAR compartmentalization. Here, we report that the reduction of Kif5b, the heavy chain of kinesin-1, protected neurons against NMDA-induced excitotoxicity and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Ischemic/hypoxic injury facilitates glutamate release and increased Ca ++ levels in the cytoplasm. Blocking NMDA receptors inhibits the inward flow of calcium ions and reduces neuronal injury (Lin et al, 2019). We previously demonstrated that MK801 reduced Glu-activated Ca ++ influx in neuronal cells expressing the Ca ++ probe gCaMP5 .…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic/hypoxic injury facilitates glutamate release and increased Ca ++ levels in the cytoplasm. Blocking NMDA receptors inhibits the inward flow of calcium ions and reduces neuronal injury (Lin et al, 2019). We previously demonstrated that MK801 reduced Glu-activated Ca ++ influx in neuronal cells expressing the Ca ++ probe gCaMP5 .…”
Section: Discussionmentioning
confidence: 99%
“…Specific kinesins also directly control the endosomal transport of NMDA receptors. The surface expression of extrasynaptic NMDA receptor depends on KIF5B, which may involve endosomes [69]. In contrast, KIF21B affects the surface expression of synaptic NMDA receptor in recycling endosome by constraining the dynamics of Neurobeachin [28].…”
Section: Kinesins In the Regulation Of Synaptic Development Transmiss...mentioning
confidence: 99%
“…Evidence shows that inhibition of KIF5b expressions has resulted in reduced excitotoxicity induced by NMDA, hence exerting a neuroprotective effect. 54 Low levels of KIF5b inhibit calcium channels preventing Ca 2+ influx inside the neuron. To this pipeline, a study has reported the effect of various antineoplastic agents on kinesin-1 and rationalized its implication for neuropathy.…”
Section: Nmda Receptors System: a Key Player In The Pathophysiology O...mentioning
confidence: 99%
“…But a study has shown that, in peripheral nerve-injured rats, there was no change in expression of KIF5B in DRG . KIF5b has been revealed to regulate extra-synaptic NMDAR distribution and signaling. , The NR2B subunit of extra-synaptic NMDAR binds to the C terminus of the KIF5b tail. Evidence shows that inhibition of KIF5b expressions has resulted in reduced excitotoxicity induced by NMDA, hence exerting a neuroprotective effect .…”
Section: Kinesin-nmda Interplay: Underpinning the Neurobiological Int...mentioning
confidence: 99%